THE IMPORTANCE OF SUFISM VALUES IN THE DEVELOPMENT OF NATIONAL PEDAGOGY - Ulug‘ov Jasur Nasirdinovich (Bright Mind Publishing, 2025)
The philosophical study of moral and spiritual heritage, along with its integration into the youth’s mindset, remains crucial today. Global threats, such as nuclear weapons, extremism, terrorism, and destructive ideologies, endanger national values. In the face of rapid economic reforms, the decline of empathy, kindness, and respect, alongside a rise in greed and deceit, highlights the urgency of focusing on youth education. Promoting national traditions and emphasizing humanitarian values, as seen in Islam, is essential. Sufism, a key Islamic science, has played a vital role in elevating spiritual values, fostering love, compassion, and spiritual resilience throughout history.
Keywords: National pedagogy, mystical values, spiritual education, perfect person, moral education.